KPU’s Strategy in Overcoming Double Data Issues in the Registration of 2024 Electoral Participants in Mojokerto City - Sabilah, Ammaya; Nurjaman, Asep (ARISTO, 2024)
This article highlights the strategies employed by the General Election Commission (KPU) to address the issue of double data that emerged during the registration process of the 2024 General Election participants in Mojokerto City. This issue stems from the ineffectiveness of the Political Party Information System (SIPOL), evidenced by thousands of double data on party membership. Double data issues can pose a severe threat to the integrity of democratic elections. Hence, this research focuses on the KPU's efforts or strategies to maintain the accuracy and reliability of data. The formulation of these strategies prioritizes the implementation of the Electoral Governance Theory, with the primary focus on analyzing and finding solutions to existing issues. This research applied a qualitative approach with a case study model. Data was collected through observation, in-depth interviews, and documentation. The results of this research indicate that based on Decree No. 260 of 2022, KPU has conducted Administrative Verification to identify potential cases of dual memberships and ineligible memberships. This process involves four main stages, including registration, administrative verification, factual verification, and determination. This research also aims to discover the issues faced by the General Election Commission (KPU) of Mojokerto City during the verification process.Â